2019
DOI: 10.5539/gjhs.v11n14p46
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Perceived Stress Among Economics Education Undergraduate Students in South-East, Nigeria

Abstract: The study objective was to examine gender differences in perceived stress among Economics Education students in federal universities in South-East Nigeria. A cross-sectional survey was adopted which consists of 135 Economics Education undergraduate students. Data collection was done using the Perceived Stress Questionnaire (PSQ). Cronbach alpha reliability of the PSQ was 0.83. Data collection was done through direct delivery of the questionnaire. Data were analyzed using mean, standard deviation and t-test. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The purpose of this research was to examine the effect of a rational emotive education (REE) on stress among undergraduate students of religious education program in Nigeria. Just as in previous studies which reported the incidence of stress among students, [6][7][8][9][10][47][48][49][50] a high-level of stress was seen among the undergraduate students of religious education program at the start of the study. However, after administration of the REE treatment, a significant reduction in mean stress of the students in the treatment group was observed and this positive result was maintained at follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…The purpose of this research was to examine the effect of a rational emotive education (REE) on stress among undergraduate students of religious education program in Nigeria. Just as in previous studies which reported the incidence of stress among students, [6][7][8][9][10][47][48][49][50] a high-level of stress was seen among the undergraduate students of religious education program at the start of the study. However, after administration of the REE treatment, a significant reduction in mean stress of the students in the treatment group was observed and this positive result was maintained at follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…Nwokenna et al (2019a) reported that there exists stress among students. Ogbueghu et al (2019) reported no gender differences in perceived stress among undergraduate students of Economics Education. Nwokenna et al (2019b) also revealed that undergraduate students experience stress in their effort to overcome academic challenges confronting them.…”
Section: Discussionmentioning
confidence: 89%